A study on tree bark samples for atmospheric pollution monitoring - Eliane Conceição dos Santos; Vera Akiko Maihara; Frederico Antonio Genezine; Mitiko Saiki (Brazilian Journal of Radiation Sciences)
Tree barks are considered a promising indicator of air pollution monitoring, because of its accumulation of aerosol particles, simplicity of species identification and wide geographical distribution. However, there are no established protocols for its sampling as well as there are no detailed studies on its usability as an alternative or complementary indicator of atmospheric pollution. In this study, barks from very common tree species, Sibipiruna (Poincianella pluviosa) and Tipuana (Tipuana tipu), were analyzed to define experimental conditions for their use as biomonitor of air pollution. Bark samples collected at the São Paulo city were cleaned and ground for analysis. Instrumental neutron activation analysis (INAA) was applied for the determination of As, Br, Ca, Co, Cr, Fe, K, Sb, Sc and Zn and graphite furnace atomic absorption spectrometry (GF AAS) for Cd and Pb. Results obtained in these analyses indicated that species of trees, bark surface layers taken for analysis as well as tree trunk diameter or tree age should be considered for use tree bark as a biomonitor. Analytical control of results carried out by analyzing certified reference materials demonstrated that INAA and GF AAS techniques can provide reliable data for element concentrations with standardized differences, |Enscore | < 1.